Respuestas

2013-08-03T18:33:30+02:00
Lalita,

Vamos a traducir paso a paso lo dice el enunciado
Actual:
                F = 1/3A                              3F - A = 0             (1)
Hace 10 años:
               (F - 10) = 1/4(A - 10)
               4F - 40 = A - 10                     4F - A = 30           (2)
Resolviendo el sistema (1) (2)
                        (1)x(-1)                     -  3F + A = 0          (1.1)
                      Sumando (2) + (1.1)                F = 30
                        En (1)           3x30 - A = 0     A = 90

Edades (años):
                 Felipe = 30
                 André  = 90